A cryogenic air separation process based on self-heat recuperation for oxy-combustion plants. (15th January 2016) - Fu, Qian; Kansha, Yasuki; Song, Chunfeng; Liu, Yuping; Ishizuka, Masanori; Tsutsumi, Atsushi
Highlights: Self-heat recuperation technology was applied on cryogenic air separation process. Both the sensible and latent waste heat was recirculated in the proposed process. Energy requirement was reduced by 20.2% by using self-heat recuperation technology. Abstract: An advanced cryogenic air separation process for oxy-combustion is proposed, based on self-heat recuperation technology. In contrast to double columns in the conventional cryogenic air separation process, a single distillation column only is used in the proposed process. By using self-heat recuperation technology, the heat of N2 product gas from the top of the single distillation column is recirculated by exchanging heat with the liquid O2 in the bottom and feed streams, largely reducing the energy requirement. The simulation results showed that the energy requirement of the proposed cryogenic air separation process was reduced by 20.2% compared with the conventional process when producing O2 with low purity (95 mol%). The influence of compressor efficiency, minimum temperature difference in the main condenser and the O2 product purity on the energy requirement were also investigated.